Eargle's Microphone Book: From Mono to Stereo to Surround : A Guide to Microphone Design and Application - Rayburn, Ray A. (Focal Press/Taylor & Francis Group, 2012)
Eargle's Microphone Book is the only guide you will ever need for the latest in microphone technology, application and technique. This new edition features more on microphone arrays and wireless microphones, new material on digital models; the latest developments in surround; expanded advice on studio set up, recording and mic selection. Ray A. Rayburn provides detailed analysis of the different types of microphones available and addresses their application through practical examples of actual recording sessions and studio operations. The book takes you into the studio or concert hall to see how performers are positioned and how the best microphone array is determined. Problem areas such as reflections, studio leakage and isolation are analyzed from practical viewpoints. Creative solutions to stereo sound staging, perspective, and balance are covered in detail. Eargle's Microphone Book is an invaluable resource for learning the 'why' as well as the 'how' of choosing and placing a microphone for any situation.